LINGUOCULTUROLOGICAL AND COGNITIVE ANALYSIS OF PHRASEOLOGY - Bekiyeva Malika Jamoldin kizi (European Journal of Humanities and Educational Advancements, 2022)
This article discusses the linguocultural and cognitive interpretation of phraseology. The analysis of our study helped to deepen the study of cultures and languages based on the linguocognitive and linguocultural approach of phraseology, as well as to fully realize the goals and objectives of the study